Outcomes of patients with systemic lupus erythematosus treated with belimumab: a post hoc efficacy analysis of five phase III clinical trials by British Isles Lupus Assessment Group-based Combined Lupus Assessment criteria - Ronald F van Vollenhoven; Shereen Oon; Mandana Nikpour; Ioannis Parodis; Eric Morand; Adrian Levitsky; Julius Lindblom; Nurşen Çetrez; Leonardo Palazzo; Henri Ala (RMD Open)
Objectives To determine belimumab efficacy assessed using the British Isles Lupus Assessment Group (BILAG)-based Combined Lupus Assessment (BICLA) in patients with systemic lupus erythematosus (SLE) from phase III belimumab randomised controlled trials (RCTs).Methods A post hoc analysis was carried out on five RCTs in active adult SLE: four with intravenous (BLISS-52, BLISS-76, BLISS-NEA, EMBRACE) and one with subcutaneous belimumab (BLISS-SC). The 52-week landmark assessments were analysed across trials. Treatment response was defined according to BICLA criteria (BILAG improvement; no worsening of disease activity based on BILAG and Systemic Lupus Erythematosus Disease Activity Index-2K; no deterioration in Physician’s Global Assessment ≥0.3 (scale: 0–3); no treatment failure).Results A total of 3086 patients received belimumab (n=1869) or placebo (n=1217). BICLA response frequencies at week 52 were greater with belimumab vs placebo in BLISS-52 (OR (95% CI): 1.49 (1.05–2.12); p=0.024), BLISS-NEA (1.62 (1.12–2.33); p=0.010) and BLISS-SC (1.89 (1.39–2.57); p<0.001). A highly significant difference was observed in the pooled population (1.47 (1.25–1.72); p<0.001; adjusted for trial variance). Belimumab yielded greater BICLA response frequencies than placebo irrespective of baseline glucocorticoid dose (>7.5 or ≤7.5 mg/day of a prednisone equivalent), in patients with baseline SLEDAI-2K≥10 and in patients with positive anti-double-stranded (ds)DNA and/or low C3/C4 levels at baseline. Belimumab combined with anti-malarials yielded greater frequency of BICLA response attainment.Conclusions In this analysis of five RCTs evaluating belimumab in SLE, belimumab conferred superiority over placebo to yield BICLA response in the overall study population and in subgroups of patients with high global or serological activity at baseline. The benefit of belimumab was more prominent when combined with anti-malarials.